2018
DOI: 10.2116/analsci.18p176
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-free Gold-silver Core-shell Nanozyme Immunosensor for the Detection of Haptoglobin

Abstract: Nanoparticles have been widely developed and shown to have intrinsic enzymatic ability, and are used in biosensors. Compared to biological enzymes used in biosensors, which are expensive and tedious to harvest, enzyme-mimic nanoparticles or nanozymes are both more stable and sensitive. An important area in this work is the development of a simple detection principle of immunosensor based on the one-step synthesis of silver nanoparticle seeded onto a gold core. The gold-silver core-shell nanoparticle acts as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 71 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Colorimetric sensors using nanoparticles in the food industry for the detection of sulfites (Qin et al, 2014) as well as their use in immunoassays (ELISA) have already been developed. As biogenic nanoparticles require no enzyme or H 2 O 2 addition, it opens up their use to a wide range of applications (Asati et al, 2009; Mohamad et al, 2018). Our results showed that the biogenic PdNPs produced by D. alaskensis G20 exhibit potential application for developing colorimetric sensors as it showed specificity for substrates depending on the pH; ABTS at low pH (pH 3), 2,6-DMP and neutral (pH 7) and TMB in a biological pH range (pH 5–7).…”
Section: Discussionmentioning
confidence: 99%
“…Colorimetric sensors using nanoparticles in the food industry for the detection of sulfites (Qin et al, 2014) as well as their use in immunoassays (ELISA) have already been developed. As biogenic nanoparticles require no enzyme or H 2 O 2 addition, it opens up their use to a wide range of applications (Asati et al, 2009; Mohamad et al, 2018). Our results showed that the biogenic PdNPs produced by D. alaskensis G20 exhibit potential application for developing colorimetric sensors as it showed specificity for substrates depending on the pH; ABTS at low pH (pH 3), 2,6-DMP and neutral (pH 7) and TMB in a biological pH range (pH 5–7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BSA as a blocking agent is well studied and widely used in developing biosensors evincing their credibility as a blocking agent. 24,25 pH dependant study of ECL system…”
Section: Selection Of the Materials For The Biosensor Developmentmentioning
confidence: 99%
“…The previous decade has seen the development of impressive biosensors that allow for sensitive and selective detection of multiple biomarkers without extensive prerequisites. [9][10][11][12][13][14][15] Conventional diagnostic techniques like immunoassays, agglutination, polymerase chain reaction (PCR), pathogen culturing among others, involve expensive and complex equipment, as well as require trained professionals to handle the system. 16 In addition, they are costly to prepare, operate, and maintain; therefore, they are not user-friendly and not easily accessible to those in under-developed areas.…”
Section: Introductionmentioning
confidence: 99%
“…The previous decade has seen the development of impressive biosensors that allow for sensitive and selective detection of multiple biomarkers without extensive prerequisites. 9–15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation